ANALISIS FAKTOR YANG MEMPENGARUHI KEPUTUSAN SECTIO CAESAREA (SC) PADA IBU BERSALIN DI RSU SUNDARI - Kasum, Nurhadimah (Jurnal Inovasi Kesehatan Masyarakat, 2025)
Every woman wants her birth process to run smoothly and normally. The birthing process can be spontaneous, but there is also a birthing process that has problems so that an operation called a caesarean section is required. This research aims to analyze the factors that influence the decision to caesarean section among women giving birth at Sundari RSU Medan in 2023. Quantitative (type) and section latitude (design). Mothers giving birth at RSU Sundari Medan (population). The bivariate test obtained results of maternal age, choice of birth date, history of SC delivery and complications during pregnancy. The multiple logistic regression test showed that the variable that had the most influence on the decision to have a caesarean section was complications during pregnancy. It is recommended to mothers in labor that mothers in labor dig up information regarding childbirth via caesarean section so that later they can make appropriate birth decisions that are correct and in accordance with the condition of the mother and baby and to staff, especially at the midwifery clinic at RSU Sundari Medan, so that they can correctly and appropriately carry out anamnesis and examination of pregnant women because it will have an impact on the type of delivery.